God and Universities - John B Cobb Jr (Journal for the Study of Religion)
In this article, ‘God and Universities’, I argue that the exclusion of God from contemporary academia did not come about because of evidence or argument. Rather, it is due to the fact that the scientific adherence to the treatment of the objective world as self-contained, was increasingly applied to everything. Also the limiting of acceptable thinking to topics falling within one academic discipline or another had no place for continuing a discussion of the topic. The self-assurance of academia is beginning to weaken. The exclusion of God as a causal factor, is part of the exclusion of purpose including human purpose. This leads to implausible explanations that are assumed to be needed but rarely explicitly defended. If the evidence for the importance of subjective experience is allowed, the door will be opened to changes that eventually could reinstate God.